2003
DOI: 10.1645/ge-3155
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny and Surface Morphology of Marine Aseptate Gregarines (Apicomplexa): Selenidium Spp. And Lecudina SPP

Abstract: Many aseptate gregarines from marine invertebrate hosts are thought to have retained several plesiomorphic characteristics and are instrumental in understanding the early evolution of intracellular parasitism in apicomplexans and the phylogenetic position of cryptosporidians. We sequenced the small-subunit (SSU) ribosomal RNA genes from 2 archigregarines, Selenidium terebellae and Selenidium vivax, and 2 morphotypes of the marine eugregarine Lecudina polymorpha. We also used scanning electron microscopy to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
106
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(115 citation statements)
references
References 34 publications
9
106
0
Order By: Relevance
“…On the other hand, the spermatozoon of Lumbrineris sp. from Grappler Inlet, Vancouver Island (Leander et al 2003), compared with those of the species so far studied (Rouse 1988;Messina et al 2005), differs greatly in external morphology, in size of the nucleus, which is rather elongated, and in number and shape of mitochondria. These findings highlight the considerable variability of form and structure of sperm in similar polychaetes species which inhabit distant seas and oceans, as noted also by our previous studies (Conti et al 2005).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…On the other hand, the spermatozoon of Lumbrineris sp. from Grappler Inlet, Vancouver Island (Leander et al 2003), compared with those of the species so far studied (Rouse 1988;Messina et al 2005), differs greatly in external morphology, in size of the nucleus, which is rather elongated, and in number and shape of mitochondria. These findings highlight the considerable variability of form and structure of sperm in similar polychaetes species which inhabit distant seas and oceans, as noted also by our previous studies (Conti et al 2005).…”
Section: Discussionmentioning
confidence: 87%
“…Messina et al (2005) recently demonstrated the close relationship between free-spawning and the ect-aquasperm morphology in a population of Lumbrineris (Scoletoma) impatiens (Claparède, 1868) (Lumbrineridae) from the Gulf of Naples (Italy), by in vitro experiments on fertilization and by TEM observations. Furthermore, Leander et al (2003) studied the phylogeny of Lecudina spp., a marine gregarine parasite of Lumbrineris sp. from Grappler *Correspondence: Gabriele Conti, Department of Cytomorphology, University of Cagliari, Cittadella Universitaria, I-09042 Monserrato (CA), Italy.…”
Section: Introductionmentioning
confidence: 99%
“…3), the only other SSU rDNA sequences from lecudinid gregarines that possess a prominently elongated mucron (Leander et al, 2003b). Like the sequences from T. nothriae, the sequences from the two morphotypes of L. polymorpha were highly divergent relative to the other known gregarine sequences.…”
Section: Discussionmentioning
confidence: 90%
“…This genus has emerged as a ''catch-all" taxon for marine aseptate gregarines that inhabit the intestines of polychaetes (and a few other host taxa). Consequently, the actual diversity of these parasites is greatly underestimated, and the identity and composition of Lecudina has become even more ill-defined within the context of modern molecular phylogenetic and comparative ultrastructural data (Leander et al, 2003b;Leander, 2008;Rueckert and Leander, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation